1999
DOI: 10.1046/j.1365-2958.1999.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimurium leucine‐rich repeat proteins are targeted to the SPI1 and SPI2 type III secretion systems

Abstract: Salmonellae encode two virulence‐associated type III secretion systems (TTSS) within Salmonella pathogenicity islands 1 and 2 (SPI1 and SPI2). Two Salmonella typhimurium genes, sspH1 and sspH2, that encode proteins similar to the Shigella flexneri and Yersinia species TTSS substrates, IpaH and YopM, were identified. SspH1 and SspH2 are proteins containing leucine‐rich repeats that are differentially targeted to the SPI1 and SPI2 TTSS. sspH2 transcription was induced within RAW264.7 macrophages, and was depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
321
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(328 citation statements)
references
References 63 publications
7
321
0
Order By: Relevance
“…We used the bacterial species S. bongori and E. coli Mutaflor as heterologous hosts in the present study. We observed that various virulence factors of S. enterica are absent in S. bongori, most importantly the SPI2 locus (20,34) and various loci encoding effector proteins of the SPI2-encoded T3SS (16,24,31). Mutaflor is an E. coli strain that is nonpathogenic but, in contrast to common lab strains, fully capable of colonizing the intestine.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We used the bacterial species S. bongori and E. coli Mutaflor as heterologous hosts in the present study. We observed that various virulence factors of S. enterica are absent in S. bongori, most importantly the SPI2 locus (20,34) and various loci encoding effector proteins of the SPI2-encoded T3SS (16,24,31). Mutaflor is an E. coli strain that is nonpathogenic but, in contrast to common lab strains, fully capable of colonizing the intestine.…”
Section: Resultsmentioning
confidence: 97%
“…There are also the translocated effector proteins SseF and SseG encoded within the SPI2 locus that colocalize with the endosomal membrane compartments after translocation by intracellular Salmonella (25). All of the SPI2-specific effector proteins currently known are absent in S. bongori (16,24,31). The total number of genes encoding translocated effectors is not known, and the function of the identified effector proteins is only partially understood.…”
mentioning
confidence: 99%
“…It is common that a bacterial pathogen codes for numerous effectors but the presence of multiple paralogs of a specific translocated effector in the same organism is only occasionally found (28)(29)(30). The close similarity among proteins in a family points to functional redundancy, which may provide an explanation for the failure to identify these proteins in previous genetic screens for bacterial mutants defective in intracellular growth.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these effectors engage and manipulate the host actin cytoskeleton machinery to facilitate bacterial internalization into host cells (3,(7)(8)(9)(10)(11). The translocation of these effectors through the host plasma membrane requires Salmonella SipB, SipC, and SipD (12)(13)(14)(15)(16).…”
Section: Salmonella Enterica Serovar Typhimurium (S Typhimurium)mentioning
confidence: 99%